TINJAUAN TERHADAP PEMENUHAN HAK-HAK KONSUMEN OLEH PENJUAL KARTU DATA INTERNET DI KOTA PEKANBARU - Kurniawan, M. Hapis; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Internet services is very necessary to support daily activities. So don’t be surprised if there are manyoutlets that sell internet cards. Currently in the sale of internet data cards, there are often problems thatharm consumers such as the delivery of incorrect information by business actors to consumers. Thisinformation includes information about card activation, number of data packages, data packet time division,and expiration. The purpose of writing this essay, namely; First, fulfillment of consumer rights by internetdata card sellers. Second, the application of the principle of good faith by internet data card sellers. Third,legal protection against violations of consumer rights by internet data card sellers.This type of research can be classified in the type of sociological juridical research, because in thisstudy the author immediately conducted research on the location or place under study. This research wasconducted at the internet data card sales counters spread in Tampan District, Pekanbaru City. While thepopulation and sample are all parties related to the problems examined in this study. Data sources used areprimary data, secondary data and tertiary data. The data collection techniques in this study wereobservation, interviews, questionnaires and literature.From the results of the problem research there are three main things that can be concluded. First, thefulfillment of consumer rights by business actors has not been fully implemented. Consumer rights that arenot fulfilled include the right to correct, clear and honest information regarding the condition and guaranteeof goods; the right to hear opinions and complaints about the goods used; the right to be treated or servedcorrectly and honestly; and the right to get compensation, compensation and / or reimbursement. Second,the application of the principle of good faith in carrying out business activities as required by the UUPK hasnot been properly implemented by business actors. The majority of business people do not know the termgood faith. However, he is more familiar with the term honesty in carrying out business activities. Butdespite knowing about honesty, in practice this is often forgotten. Third, business actors are responsible forconsumer losses. The responsibility is in the form of a re-explanation of the product and compensation in theform of refunds or replacement of goods. Suggestion from the Author, First, education and awareness ofconsumers and business actors must be cultivated because it is very important. A consumer must know hisrights so that he can demand fulfillment of these rights to the seller. Second, the obligation to have goodintentions in carrying out business activities must be understood correctly by business actors. Businessactors may not take profits at the expense of others. Third, there must be socialization carried out byrelevant agencies regarding the Consumer Protection Act.Keywords: Consumer Rights - Obligations of Business Actors - Good Faith - Responsibility